Kajian Teknis Lemparan Flyrock pada Pit 303 Jembayan PT Pamapersada Nusantara Distrik Baya Kabupaten Kutai Kartanegara Kalimantan Timur - Asep Triyanda; Raimon Kopa (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. To consider the safe distance of the tool when blasting requires analysis and prediction of flyrock throw. Methods for predicting flyrock throws are Richard & Moore's empirical method and Ebrahim Ghasemi's dimensional analysis. The observation results of the blasting activity were 36 times, and the farthest was 98.87 m of flyrock. The research objective is to analyze the blasting geometry design to better control the flyrock throw, so that the target safe radius of the tool can be reduced from 200 m to 100 m. Prediction of actual flyrock throw using the empirical method Richard & Moore obtained a face burst deviation of 32.68 m, 25.43 m cratering, and 15.12 m rifling, with an error percentage of 69.93%, 30.38%, and 30.64% . Meanwhile, the deviation of Ebrahim Ghasemi's dimensional analysis method is 6.23 m with an error percentage of 9.85%. Based on statistical analysis, stemming has a very strong effect on flyrock throwing, namely 71.40%. Ebrahim Ghasemi's dimensional analysis method is better to predict the actual flyrock throw. To control the actual flyrock throw, a minimum stemming is recommended according to the diameter and depth of the blast hole based on the scaled depth of burial equation, and considering the prediction of a maximum flyrock throw of 50 m and a powder factor not to exceed 0.17 kg / m3. By using these recommendations the safe radius of the tool can be reduced to 100 m with the resulting flyrock safety factor not approaching or exceeding the safe radius of the target, which is 100 m.Keywords: Flyrock, Scaled Depth of Burial, Safe Radius, Stemming